PENGARUH STRES KERJA DAN KONFLIK PERAN TENAGA MEDIS TERHADAP KINERJA PERAWAT WANITA PADA RUMAH SAKIT BHAYANGKARA KOTA BENGKULU - Putera, Aniko; Sismanto, Adi (UM. Bengkulu, 2024)
This study aims to determine the effect of work stress and role conflict of medical personnel on the performance of female nurses at Bhayangkara Hospital, Bengkulu City. This type of research is a survey research with a quantitative approach, the object of this research is female nurses at Bhayangkara Hospital. The sampling method is non-probability technique, namely the incidental sampling technique. The number of respondents in this study were 44 people. Methods of data collection using a questionnaire. By using analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Testing namely t test and f test. The results of this study can be concluded that the variable Job Stress has a positive effect on nurse performance, Conflict of the Role of Medical Personnel has a positive effect on the Performance of Female Nurses at Bhayangkara Hospital, Bengkulu City. Keywords: Job Stress, Role Conflict, Nurse Performance